Qaran Tabrizi's poems in Lubab ul-Albab - تهمینه عطایی کچویی; شهره معرفت (تاریخ ادبیات)
‌Biography writing is the first form of Persian literary history, and biographies, in any form, are useful for reaching some parts of the history of literature and are the basis of today's researchers' work. Among the Persian biographies, Lubab ul-Albab, written by Muhammad Aufi, is the first Persian biography and was written around 618 AH. In the second volume of this biography, the author spoke about 169 poets and gave a selection of their poems. Among these poets, Qatran Tabrizi is a famous poet of the 5th century, who was mentioned by Aufi under "Chapter 3 on the mention of the poets of Iraq and its regions". Qatran's poems in this ‌biography are 74 verses and include a composition and a qasida. In order to correct Qatran’s Diwan, whose old manuscript has not been known until today, studying and examining his poems in biographies, especially in Lubab ul-Albab, is one of the essential and primary tasks. By comparing the available versions of his Diwan, the authors have come to differences, examples of which are presented here.